Inequality over the Past Century - Gonzalez Alvaredo, Facundo (2011)
The share of income received by the top 1 percent of earners varied markedly between 1900 and 2008 in 24 developed and developing economies. Moreover, the biggest earners changed as well. When the century began, the top 1 percent was dominated by capital owners. By the end of the century the hired hands—the top executives—shared with capital owners the highest part of the income distribution.